Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Jamaah pada Penyelenggara Perjalanan Ibadah Umrah (PPIU) di Jakarta Timur: The Effect of Service Quality and Price on Pilgrim Satisfaction at Umrah Travel Organizers (PPIU) in East Jakarta - Della Amalia Prasetiyo; Ade Sri Mulyani (PT Cakrawarti Empat Proksi, 2026)
Increasing competition among Umrah Pilgrimage Tour Operators (PPIUs) in East Jakarta following the pandemic is still accompanied by complaints regarding service quality and price. This study aims to analyze the partial and simultaneous effects of service quality and price on pilgrim satisfaction. Using a quantitative approach, primary data were collected from 100 respondents via Likert-scale questionnaires between May and June 2026 using a purposive sampling technique based on the Lemeshow formula. Data were processed using SPSS 27 through validity, reliability, classical assumption, multiple linear regression, t-test, f-test, and coefficient of determination tests. The results show that service quality and price have a positive and significant effect on pilgrim satisfaction, both partially and simultaneously, with the price variable as the most dominant factor. Together, both variables contribute 90.2% to pilgrim satisfaction. This study concludes that transparent pricing and maintaining consistent service quality are key strategies for maintaining pilgrim satisfaction at PPIUs.